2015
DOI: 10.4062/biomolther.2015.075
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat Induces Apoptosis through a Mitochondria-Dependent Pathway in RAW264.7 Cells

Abstract: Paraquat dichloride (N,N-dimethyl-4-4′-bipiridinium, PQ) is an extremely toxic chemical that is widely used in herbicides. PQ generates reactive oxygen species (ROS) and causes multiple organ failure. In particular, PQ has been reported to be an immunotoxic agrochemical compound. PQ was shown to decrease the number of macrophages in rats and suppress monocyte phagocytic activity in mice. However, the effect of PQ on macrophage cell viability remains unclear. In this study, we evaluated the cytotoxic effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Previous studies have shown that cells deficient in Ogg1 and Mutyh are sensitive to oxidants, in part because of the negative effects of oxidative stress on cell-cycle progression [3]. These observations are in accord with studies showing that increased levels of ROS are associated with cell death [22, 42, 43], as well as DNA damage [44]. There should be a substantial increase in ROS levels when cells are severely repair-deficient.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies have shown that cells deficient in Ogg1 and Mutyh are sensitive to oxidants, in part because of the negative effects of oxidative stress on cell-cycle progression [3]. These observations are in accord with studies showing that increased levels of ROS are associated with cell death [22, 42, 43], as well as DNA damage [44]. There should be a substantial increase in ROS levels when cells are severely repair-deficient.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have documented the ability of PQ to redox cycle resulting in generation of ROS and extensive mitochondrial damage [1719]. Among the different ROS, the superoxide anion radical, has been observed and reported [2, 1922]; H 2 O 2 has also been observed being induced in a dose-dependent manner [22, 42, 43]. ROS-dependent cell death was also reported in other cultured mammalian cells, such as human promyelocytic leukemia HL-60 cells [22], RAW264.7 cells [42], and human neutrophils [43].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in mitochondrial membrane potential (MMP) were evaluated using the JC-1 Mitochondrial Potential Assay Kit (Beyotime). Mitochondrial depolarization occurring in the early stage of apoptosis was evidenced by a fluorescence emission shift from green (JC-1 monomer) to red (J-aggregate), and the results showed potential-dependent accumulations in mitochondria ( Jang et al ., 2015 ). K562 cells were seeded in a 6-well plate at 2×10 5 cells per well and then treated with chaetominine (0, 25, 50 or 100 nM) for 24 h or 48 h. Approximately 10 5 cells were harvested, incubated in dye-containing medium, and washed twice in staining buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Both in vivo and in vitro reports with PQ induced caspase-3 activation in brain cells are consistent with our ndings. 51 Moreover, the AKT/PI3K pathway plays a central role in integrating various cellular stimuli with a broad range of cellular functions. AKT further regulates an array of downstream targets involving cell survival, cell growth and cell proliferation, including members of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 99%